Effect of Green Additives in Copper Electrorefining Bath: Current Efficiency and Surface Characterization Investigation - F. M. A. Abouzeid; S. Alshammery (Journal of Chemistry)
The copper electrorefining performance in acidified copper sulfate solution utilizing the potential-dynamic polarization technique was established. This was inspected through measurement and comparison of limiting current-cathode potential relationship in a solution of regularly rising methanolic extract concentrations (from 50 to 1000 ppm) of Lablab purpureus (Dolichos lablab), Linseed (Linum usitatissimum), Sidr leaves (Ziziphus spina-christi), and Indian costus (Saussurea costus). The impact of temperature on the copper electrorefining kinetic was studied. There is a reduction in the limiting current values via developing plant extract concentration while there is a growth in limiting current values via temperature boosting (293–313 K). This proves that copper species mass transport from the electrolyte bulk toward the cathode surface is the slowest step in electrolyte including various concentrations of the plant extract investigated. The values of activation energies prove that the refining procedure rate was diffusion controlled. Surface morphologies of copper samples were assessed via a scanning electron microscope (SEM) and atomic force microscope (AFM). The chemical composition of the investigated methanolic plant extract was estimated by gas chromatography–mass spectroscopy (GC–MS). Adding elevated methanolic plant extract concentration (1000 ppm) to the refining bath is extremely valuable in improving surface features and appears to have a promising influence. The leveling and grain refining effects were identified. A copper-deposited film with low roughness and high flatness may be obtained. Antimicrobial screening suggests that all-natural product substances demonstrated mild to great action versus the examined organisms. The cathodic current efficiency was decidedly enhanced by improving plant extract concentration in the bath from 200 to 1000 ppm.